A novel self-cleaning functional composite coating with extraordinary anti-corrosion performance in high pressure CO2 conditions. (29th September 2022) - Luo, Hongxin; Wang, Chijia; Liu, Shuyi; Liu, Shupei; Fan, Weihao; Wang, Zihua; Xie, Deyuan; Wang, Huaiyuan
Abstract: This study demonstrates an alternative method for fabricating a novel integrated anticorrosion self-cleaning functional coating using the GO nanosheets with the TiO2 –ZnO heterostructure to effectively induce charge separation and to accomplish photoinduced hydrophilic conversion. Through ultraviolet light (UV) irradiation, the PFDTMS-modified filler transformed from hydrophobic to hydrophilic, while the fluorine groups on the surface of the filler still existed. Research of EIS shows that the impedance at 0.01 Hz of 20% F/T-Z-G Polyurea coating was about 1 × 10 3 times higher than polyurea coatings, after 24 h of immersion in 2.8 MPa, 110 °C pure CO2 and NaCl solution. The results demonstrate that F/T-Z improves the dispersion of GO and make the polyurea matrix denser, inhibiting the diffusion of corrosive medium. Additionally, the GO and fluorine groups strengthen the shielding performance of the coating. Moreover, the TiO2 –ZnO heterojunction traps H2 O molecules to form hydroxyl radicals (OH). Simultaneously, Fe 2+ and Fe 3+ combine with OH to form Fe3 O4, and the passivation film was formed on the surface of steel. It is believed that this hydrophilic-hydrophobic integrated functional coating will be an excellent candidate for technological applications, such as anticorrosion, self-cleaning materials and composite coatings. Graphical abstract: Image 1